(3JWHjbGJ eMdhdI aj GdGbJUGO GdLRFjs - (3YeGQ(B, (3YeGQjs ((3YeGf(B:s (3OGQ GdefGgL(B,s, 2002)
(3JWHjbGJ GdYQV hGdWdH hGdJhGRf(B-(3JWHjbGJ Ydi MSGH GdeQhfGJ(B-(3JWHjbGJ Ydi JhGRf GdShb(B-(3JWHjbGJ Ydi Sdhc GdeSJgdc(B-(3fXQjI GdefaYI(B-(3fXQjI efMfjGJ GdShA(B-(3JWHjbGJ Ydi Sdhc GdefJL(B-(3fXQjI GdGfJGL(B-(3fXQjI GdJcGdja(B-(3JWHjbGJ Ydi JhGRf GdefJL(B-(3Shb GdefGaSI GdJGeI(B-(3JWHjbGJ Ydi JhGRf GdefJL(B-(3Shb GdGMJcGQ GdeWdb(B-(3Shb GdefGaSI GdGMJcGQjI(B-(3Shb GMJcGQ GdbdIs
(3HHdhZQGajG U(B. 252(3; edGMb U(B. 255s
Keywords: (3GdGbJUGO GdLRFj, GdCShGb, GdeMGSHIs